2021
DOI: 10.1530/ec-20-0484
|View full text |Cite
|
Sign up to set email alerts
|

The roles of vitamin D and cathelicidin in type 1 diabetes susceptibility

Abstract: Type 1 diabetes has increasingly greater incidence and prevalence with no cure available. Vitamin D supplementation is well documented to reduce the risk of developing type 1 diabetes. Being involved in the modulation of cathelicidin expression, the question whether cathelicidin may be one of the underlying cause arises. Cathelicidin has been implicated in both the development and the protection against type 1 diabetes by mediating the interplay between the gut microbiome, the immune system and β cell functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Vitamin D is thought to be protective against the development of type I diabetes by modulating the immune system by dampening the autoimmune response, decreasing selfdestructive islet cell auto-antibodies produced by beta-cells, and, thus, preserving the betacell mass of the pancreas. In murine models of type I diabetes mellitus, supplementation with the active form of vitamin D, calcitriol, prevented the onset of diabetes, which further supported the role of vitamin D in the prevention of type I diabetes [19,20]. For type II diabetes, vitamin D was thought to enhance insulin sensitivity; however, a recent metaanalysis of 18 randomized controlled trials found no benefit of vitamin D supplementation on the markers of insulin sensitivity [21].…”
Section: Discussionmentioning
confidence: 92%
“…Vitamin D is thought to be protective against the development of type I diabetes by modulating the immune system by dampening the autoimmune response, decreasing selfdestructive islet cell auto-antibodies produced by beta-cells, and, thus, preserving the betacell mass of the pancreas. In murine models of type I diabetes mellitus, supplementation with the active form of vitamin D, calcitriol, prevented the onset of diabetes, which further supported the role of vitamin D in the prevention of type I diabetes [19,20]. For type II diabetes, vitamin D was thought to enhance insulin sensitivity; however, a recent metaanalysis of 18 randomized controlled trials found no benefit of vitamin D supplementation on the markers of insulin sensitivity [21].…”
Section: Discussionmentioning
confidence: 92%
“…Given the previously reported role of CAMP in diabetes type 1 [ 25 ], as well as the present finding of its significant increase during an OGTT, future studies might involve hyperinsulinemic-euglycemic clamp techniques in order to evaluate CAMP kinetics under conditions of elevated insulin and constant glucose levels. In particular, such approaches might elucidate putative associations of insulin sensitivity and systemic CAMP regulation.…”
Section: Discussionmentioning
confidence: 97%
“…This finding suggests a considerable short-term induction of CAMP expression and secretion by insulin, glucose, and/or incretins. Of note, CAMP has previously been reported to be linked to diabetes mellitus type 1 [ 25 ], and its circulating levels have been suggested as a marker for diabetic nephropathy [ 26 ]. While a recent study reported decreased CAMP serum concentrations in T2D patients [ 27 ], results from previously published studies are somewhat incongruent with this observation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D is a candidate for protection against T1D due to its anti-inflammatory effects, role in regulation of the immune system and induction of T regulatory cells, which modulate autoimmune risk (8). Cathelicidin was recently proposed to link vitamin D with the gut microbiota and protective effects on beta-cell function (173). Further evidence stems from the higher incident cases of T1D observed at northern latitudes and in winter months compared to summer, where sunlight exposure inversely correlates with T1D cases on a monthly basis (174).…”
Section: Vitamin Dmentioning
confidence: 99%